Alberto Caturelli, Metafísica del Trabajo, Librería Huemul, Buenos Aires, 1982, 175 pp. - Derisi, Octavio Nicolás (1983)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina